Simplifying
3.1(2f + 1.2) = 0.2(f + -6)
Reorder the terms:
3.1(1.2 + 2f) = 0.2(f + -6)
(1.2 * 3.1 + 2f * 3.1) = 0.2(f + -6)
(3.72 + 6.2f) = 0.2(f + -6)
Reorder the terms:
3.72 + 6.2f = 0.2(-6 + f)
3.72 + 6.2f = (-6 * 0.2 + f * 0.2)
3.72 + 6.2f = (-1.2 + 0.2f)
Solving
3.72 + 6.2f = -1.2 + 0.2f
Solving for variable 'f'.
Move all terms containing f to the left, all other terms to the right.
Add '-0.2f' to each side of the equation.
3.72 + 6.2f + -0.2f = -1.2 + 0.2f + -0.2f
Combine like terms: 6.2f + -0.2f = 6f
3.72 + 6f = -1.2 + 0.2f + -0.2f
Combine like terms: 0.2f + -0.2f = 0.0
3.72 + 6f = -1.2 + 0.0
3.72 + 6f = -1.2
Add '-3.72' to each side of the equation.
3.72 + -3.72 + 6f = -1.2 + -3.72
Combine like terms: 3.72 + -3.72 = 0.00
0.00 + 6f = -1.2 + -3.72
6f = -1.2 + -3.72
Combine like terms: -1.2 + -3.72 = -4.92
6f = -4.92
Divide each side by '6'.
f = -0.82
Simplifying
f = -0.82